Inkjet printing Schwann cells and neuronal analogue NG108-15 cells. (1st March 2016) - Tse, Christopher; Whiteley, Robert; Yu, Tong; Stringer, Jonathan; MacNeil, Sheila; Haycock, John W; Smith, Patrick J
Abstract: Porcine Schwann cells and neuronal analogue NG108-15 cells were printed using a piezoelectric-inkjet-printer with a nozzle diameter of 60 μ m, within the range of 70–230 V, with analysis of viability and quality after printing. Neuronal and glial cell viabilities of >86% and >90% were detected immediately after printing and no correlation between voltage applied and cell viability could be seen. Printed neuronal cells were shown to produce neurites earlier compared to controls, and over several days, produced longer neurites which become most evident by day 7. The number of neurites becomes similar by day 7 also, and cells proliferate with a similar viability to that of non-printed cells (controls). This method of inkjet printing cells provides a technical platform for investigating neuron–glial cell interactions with no significant difference to cell viability than standard cell seeding. Such techniques can be utilized for lab-on-a-chip technologies and to create printed neural networks for neuroscience applications.